The Use of Macerated Garlic (Allium Sativum L.) Oil in Preventing the Postoperative Adhesions in Rats - ÇALIŞKAN, G. Ülke; EMİN, Nuray (Bingol Universitesi, 2022)
In the present study, the efficiency of intra-abdominal use of the macerated oil obtained from Taşköprü Garlic (Kastamonu/Türkiye), which is one of the products with geographical indication-from European Union, in preventing the postoperative adhesions. The chemical structure of the macerated-oil, prepared using fresh-garlic at a concentration of 1.2 g/ml in olive oil, was analyzed by spectrophotometric and chromatographic methods. In in vivo experiments, Wistar Albino rats (n=8) were applied cecal abrasion under general anesthesia. Abrasion zone was treated with physiological saline solution in control group (K) and different doses of macerated oil (0.5-1 ml) in study groups-(S1 S2). Macroscopic-adhesion-scoring-(MAS) between 0-4 was performed for all the subjects on postoperative days 3-28. After staining the tissue-samples, which were taken from subjects found to have adhesion, histopathological adhesion scoring (HAS) was performed between 0 3. On day 3, adhesion was detected in all the subjects. The adhesions reached MAS-2 level in the K and were in MAS 1 level in the subjects in S1 S2. On day 28, no adhesion was observed in S1-S2, whereas adhesions in K remained at the level MAS-2. Moreover, HAS were found to be HAS-1 in S1 S2-K on day 3 whereas it was found to be HAS-2 in K subjects, where adhesion formation continued, on day 28. As a result, the garlic-macerated-oil, obtained by soaking fresh garlic in olive oil for a time, is a low cost and effective agent for adhesion prevention, which will be easily produced and applied by clinicians.
Keywords: Veterinary Surgery; Health Care Administration; Garlic; Histopathology; Intraabdominal; Olive Oil; Surgical Adhesions; Sağlık Kurumları Yönetimi; Veteriner Cerrahi; Cerrahi Adezyonlar; Histopatoloji; İntraabdominal; Sarımsak; Zeytinyağı; 3. Good health